Decision Support System Using Fuzzy Logic Mamdani Method To Select New Students: Decision Support System Using Fuzzy Logic Mamdani Method To Select New Students - Hadi Ansyah; Agung Triayudi; Albaar Rubhasy (Jurnal Mantik, 2020)
Produce competent graduates in the fields of science and computers with excellence in the fields of computer graphics and multimedia, computer networking, and software technology and have character and moral integrity. Decision support system can be interpreted as a system designed to support management in making a decision. The problem to be solved in this research is to develop a decision support system produced by a computer-based system that is used to help decision making in finding data and certain types of types to solve problems that are not structured. This study uses a descriptive approach to the Mamdani fuzzy logic technique. The results of this study are in the form of calculations in determining the selection of prospective students manually in mamdani fuzzy logic, the application to be built can be useful for its users in determining the selection of prospective students who will be competent in the field or academics. This method was chosen because it can provide optimal results, by selecting prospective new students